INCIDENCE OF ANTIDEPRESSANT USE AND WORK ENVIRONMENT: INTEGRATIVE REVIEW (REMUNOM, 2025)
Anxiety, panic syndrome, depression and burnout are recurrent diagnoses and can be aggravated in health professionals. Episodes considered adverse in these spaces have the potential to become negative mental triggers. Work activity is part of people's lives and can be related to feelings of pleasure and/or suffering. To discuss the prevalence of psychotropic use among health professionals in the workplace. This work is an integrative literature review. The research was carried out by selecting scientific articles published in periods indexed in the Latin American and Caribbean Literature in Health Sciences (LILACS), PubMed, Scientific Electronic Library Online (Scielo) databases, using descriptors extracted from DeCS (Health Sciences Descriptors), based on the keywords: Working conditions; occupational health; antidepressant, through the Boolean operator AND, OR and NOT. Initially, 160 articles were found in the databases searched. When the previously established inclusion criteria were applied, 06 articles were selected to be used in the analysis and discussion of the work. According to the scientific articles found, the studies show the prevalence of use of antidepressant medications in the workplace. Antidepressants, antiepileptics and antipsychotics are considered the main classes of psychotropic drugs used in the workplace. After the study carried out in research of the current published articles, it is possible to conclude that the reasons that lead some workers to use antidepressant medications are numerous, among them are working in sectors with more exhausting routines and difficult relationships with coworkers.